Bibliometric and Visual Analysis of Trends in Cosmetics: A Forensic Approach - Divita Sharma (International Journal of Medical Toxicology and Legal Medicine, 2024)
In recent years the utilization of cosmetics has exponentiated worldwide, irrespective of the gender. From the perspective of forensics, cosmetics are often found in minute quantities in crime scene. There has been a lot of research conducted on a number of cosmetic products; hence it becomes important to analyze the research trends on cosmetological advancements. The current study focuses on creating a bibliometric and visual analysis, using the software, VOSViewer. All of the studies conducted in the field are from 1972 to 2022. For this, SCOPUS database has been selected to retrieve all the studies that are related to the forensic analysis of cosmetics. Research trends were studied with respect to the publications, citations and co-citations, keywords, countries as well as authors, journals and their impact. Journal analysis was also done by calculating its CiteScore as well as SNIP, SJR and Quartile ranking. Out of the 63 shortlisted studies on the basis of their relevance, it was found that India contributed the most (28.37%) in the field, followed by USA (12.16%). The authors who were cited the most were Rajinder Singh and Vishal Sharma with 17.13% and 13.94% citations respectively. Forensic Science International was the copious as well as most cited journal. Maximum number of studies have been done on lip (38%) and hair (23%) cosmetics. The most utilized analytical technique was found to be mass spectrometry (21%) followed by ATR-FTIR (19%). The cumulative publications have increased significantly from 2014 to 2022. Henceforth, it becomes important to study the research trends of the field. To summarize, the current review studies about all the features of publications like; most dominating countries, co-cited references and keywords, influential authors, journals and trends followed in the field of forensic cosmetics.